2011
DOI: 10.1051/0004-6361/201016255
|View full text |Cite
|
Sign up to set email alerts
|

The continuum intensity as a function of magnetic field

Abstract: Context. Small-scale magnetic fields are major contributors to the solar irradiance variations. Hence, the continuum intensity contrast of magnetic elements in the quiet Sun (QS) network and in active region (AR) plage is an essential quantity that needs to be measured reliably. Aims. By using Hinode/SP disk center data at a constant, high spatial resolution, we aim at updating results of earlier ground-based studies of contrast vs. magnetogram signal, and to look for systematic differences between AR plages a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
61
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 73 publications
(98 reference statements)
33
61
5
Order By: Relevance
“…For pixel-based values, a comparison of the mean relations between the disk-center brightness contrast (with respect to the average quiet Sun) and the magnetic field strength from observations and simulations at their respective spatial resolution reveals a striking disagreement. The simulations basically show a monotonic increase of contrast with field strength , while the observations exhibit a maximum contrast (which may even be negative) at intermediate field strength (or magnetogram signal) and a decrease towards stronger field values (e.g., Title et al 1992;Topka et al 1992;Lawrence et al 1993;Narayan & Scharmer 2010;Kobel et al 2011), even if dark pores are explicitely excluded. On the other hand, if only bright features are considered, observers find increasing brightness (or saturation) with growing field strength (Viticchié et al 2010;Berger et al 2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For pixel-based values, a comparison of the mean relations between the disk-center brightness contrast (with respect to the average quiet Sun) and the magnetic field strength from observations and simulations at their respective spatial resolution reveals a striking disagreement. The simulations basically show a monotonic increase of contrast with field strength , while the observations exhibit a maximum contrast (which may even be negative) at intermediate field strength (or magnetogram signal) and a decrease towards stronger field values (e.g., Title et al 1992;Topka et al 1992;Lawrence et al 1993;Narayan & Scharmer 2010;Kobel et al 2011), even if dark pores are explicitely excluded. On the other hand, if only bright features are considered, observers find increasing brightness (or saturation) with growing field strength (Viticchié et al 2010;Berger et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…1, upper panel) to determine the I − B relation for small-scale magnetic features (i.e., excluding pores) in a plage region. The data were treated in exactly the same way as described by Kobel et al (2011) in order to obtain maps of the magnetic field and of the intensity in the red continuum of the 630.25 nm line. This included an inversion of the Stokes spectra with the VFISV code developed by Borrero et al (2011), which provides the "apparent" strength of the line-of-sight component of the field, B LOS = Bα cos γ, where B is the "intrinsic" field strength, α is the fractional amount of light that comes from the magnetized plasma, and γ is the inclination angle with respect to the observer (here, the vertical direction).…”
Section: Observational Datamentioning
confidence: 99%
“…the entire profile was used to calculate the dependencies, which should give more precise results than in Title et al (1992) and Topka et al (1992), where the combination of non-simultaneous observations in the two wings of a spectral line was used. In a newer observations by Hinode, with much higher spatial resolution and when the magnetic field strength (not flux) was obtained using inversions, Kobel et al (2011) find that the relationship between contrast and apparent longitudinal field strength exhibits a peak at around 700 G, both for the quiet Sun network and active region plage, while earlier studies only found a monotonic decrease in active regions. The contrast possibly depends on the size of magnetic elements and not on their strength (the intrinsic strength is more or less constant in the kG range).…”
Section: Introductionmentioning
confidence: 95%
“…This latter dependence makes it possible to test theoretical models by means of observations. Indeed, observations of the solar disc center given in Frazier (1971), Title et al (1992), Topka et al (1992Topka et al ( , 1997, Montagne et al (1996), Kobel et al (2011), Kostyk (2013) show that the absolute value of continuum contrast of facular regions (without considering separately granules and intergranular lanes) depends on the magnetic field, though the observational findings are somewhat contradictory. Frazier (1971) shows that the continuum contrast of the facula at the solar disc center and the magnetogram signal are correlated in a complicated manner.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation